You are Hungry: Flâneuring, Edible Mapping and Feeding Imaginations - Mikey Tomkins (Footprint)
The idea of growing food in cities, often termed urban agriculture (UA), is rapidly becoming a popular concept linked to ideas of sustainable cities. However, for most residents it is a difficult concept to visualize due to the complexity of the built environment. This research uses 32 participatory walks with 150 local residents around a 25-hectare site within east London to explore reactions to the idea of potential UA landscapes.